Vapor phase oxidation of 4-fluorotoluene over vanadia-titania catalyst - Maurya, S. K.; Patil, P.; Shubhangi B. Umbarkar; Gurjar, M. K.; Dongare, Mohan K.; Rudiger, S.; Kemnitz, E. (Journal of Molecular Catalysis A - Chemical, 2005)
The vapor phase oxidation of 4-fluorotoluene has been carried out over vanadia-titania catalysts with moderate conversion and selectivity for 4-fluorobenzaldehyde. Two series of V2O5/TiO2 catalysts with 1-10 mol% vanadia were prepared by sol-gel technique using vanadium and titanium peroxide as vanadia and titania precursors respectively and by impregnation technique using vanadium peroxide on anatase titania support. The samples were characterized by X-ray diffraction, NH3-TPD, FT-IR and BET surface area measurements. The XRD of the catalysts prepared by impregnation technique showed retention of the anatase titania whereas the catalysts prepared by sol-gel technique showed the formation of rutile titania with minor amount of anatase phase at lower vanadia content (1-3 %), which completely transformed into anatase phase at higher vanadia loading. The samples prepared by sol-gel method showed higher acidity and surface area compared to the samples prepared by impregnation. Pyridine adsorption study by FT-IR revealed the presence of Lewis acidity at lower vanadia loading (1-3 %) and presence of both Lewis as well as Bronsted acidity at higher vanadia loading. The catalytic activity for oxidation of 4-fluorotoluene increased with vanadia loading in the sol-gel catalysts. The catalysts prepared by impregnation technique were found to be less active. However the selectivity for 4-fluorobenzaldehyde decreased with increase in vanadia content. The influence of vanadia loading, reaction temperature and contact time on the catalytic activity for 4-fluorotoluene oxidation has been investigated. The structure of the catalyst and its catalytic activity has been correlated. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Catalyst; fluorotoluene; Oxidation; vanadia-titania; vapor phase